Alkalno-silikatna reakcija v betonu - Mladenovič, Ana (Kovine zlitine tehnologije, 1997)
Alkali silica reaction (ASR) is a chemical reaction between alkalies in cement and certain responsive minerals and rocks types in the aggregate. The reaction produces an expansive gel which can cause expansion and cracking of concrete. Reactive components are rocks and minerals containing metastable silica. Some more detailed data are provided about possible reactive components in the sand and gravel of the rivers Mura and Drava, based on new knowledge about ASR.
Keywords: cement; kemijske reakcije; mineral; minerali; agregati; kamnine; civil engineering; gradbeništvo; silicijev dioksid